Designing a STEM Project-Based Learning Module for Scientific Literacy and Critical Thinking Elementary School Students - Septiadevana, Riski; Abdullah*, Norazilawati (Jurnal Pendidikan Sains Indonesia, 2024)
STEM education is useful for facing 21st century competition. However, the availability of STEM project-based learning (STEM-PjBL) modules for enhancing scientific literacy and critical thinking Indonesian students is still rare, especially at the elementary school level. The objective of this study is to design a STEM-PjBL module that enhances students' 21st-century skills, specifically focusing on improving their scientific literacy and critical thinking capabilities by organizing the constructs and items within the module. This study is qualitative research at the stage of designing the content of STEM-PjBL module using literature reviews and expert interviews. The acquired data underwent thematic analysis for examination. The resulting module construct includes module objectives; module structure; module content that includes STEM components; scientific literacy components, and critical thinking components; learning aids or media; and assessment in modules with accompanying items for each construct. The resulting module construct and item are used as the basis for the next stage, namely the module development stage. This study holds significance for advancing STEM education in Indonesia and serves as a valuable asset, particularly for initiatives highlighting STEM-PjBL learning activities aimed at enhancing 21st-century skills